Pelatihan model pembelajaran seni budaya bagi Guru SD untuk meningkatkan kualitas pembelajaran di Kabupaten Bone - Awaluddin Muin (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
The application of a varied learning model of Artand Culture subjects in elementary school will have an impacton students. They will be easier in understanding subjects sothat the quality of learning will increase. The results of earlyobservations made showed that the ability of elementaryschool teachers in applying various art learning models wasstill limited. It could be seen from varied activities. As a result,the learning process was monotonous. The strategic target ofthis training activity was elementary school teachers in BoneRegency, consisting of several teachers, school operators andthe school principal. Activities that have been carried outrelated to the training of learning models of Art and Culture inthe elementary school have shown satisfactory results. It isbecause the implementation of the training program providedgreat benefits of the application of art learning models in theelementary school.